An empirical study of mobile social app continuance intention: integrating flow experience and switching costs. (2017) - Hong, Hong; Xu, Di
Recent fast advances in information technologies have dramatically expanded the use of mobile social apps (i.e., applications). Compared to other products or services, switching costs of mobile social apps are lower as a user can easily switch from one mobile social app to another. In order to figure out factors influencing users' continuance intention and provide practical implications on building users' loyalty, we integrate flow experience and switching costs to build an empirical model. Specifically, we take Wechat as an example to investigate due to its popularity in China. Survey and structural equation model (SEM) are used to test the research model. The results show that: perceived enjoyment has influence on flow experience, and further affects users' continuance intention; switching costs exert positive effect on continuance intention; flow experience exerts partial mediating effect between perceived enjoyment and continuance intention. Related theoretical and practical implications are also discussed.